Friction-resistant quick-dry odorless ink and preparation method thereof
By using modified graphite nanopowder and modified polyurethane emulsion in the ink, combined with airflow crushing technology and photochromic groups, the problems of slow drying speed and poor wear resistance of water-based ink are solved, and the rapid drying and high wear resistance of ink are achieved, and the production efficiency and aesthetics of printed materials are improved.
Patent Information
- Application Number
- CN202411550361.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The drying speed of existing water-based inks is slow, resulting in low production efficiency of printed products and poor wear resistance, which is easy to decolorize during friction, affecting the aesthetics of the packaging and secondary recycling.
Inks with modified graphite nanopowder, modified polyurethane emulsion and acrylic emulsion are nano-narrowed by secondary airflow crushing technology, combined with photochromic groups and polyol compounds, and formed a three-dimensional network structure to improve the quick-drying and wear resistance of the ink.
It realizes rapid drying of ink and high wear resistance, improves the production efficiency and aesthetics of printed materials, and reduces environmental pollution.
Smart Images

Figure BDA0005114919780000071 
Figure BDA0005114919780000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inks, in particular to a friction-resistant, quick-drying, odorless ink and a preparation method thereof. Background Art
[0002] Most of the existing environmentally friendly inks are water-based inks, that is, they use water as a solvent, thus avoiding the production of VOCs. However, compared with traditional oil-based inks, water-based inks dry more slowly, which will affect the production efficiency of printed products, thus limiting the development of water-based inks.
[0003] At present, water-based ink is often used on outer packaging. Due to the influence of various natural factors, the water-based ink printed on corrugated paper boxes has poor wear resistance during the movement of packaging boxes, and is prone to discoloration due to friction. This not only pollutes the packaging and reduces its appearance, but is also not conducive to secondary recycling, resulting in a waste of resources. More and more scientific researchers have begun to conduct increasingly in-depth research on the abrasion resistance of water-based inks. Summary of the invention
[0004] The purpose of the present invention is to provide a friction-resistant quick-drying odorless ink and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a friction-resistant quick-drying odorless ink, which comprises, by weight, 8 to 12 parts of modified graphite nanopowder, 25 to 35 parts of modified polyurethane emulsion, 20 to 30 parts of acrylic emulsion, 10 to 15 parts of water, 0.1 to 0.3 parts of silicone leveling agent, 3 to 5 parts of colorant, 0.1 to 0.3 parts of silicone defoaming agent, and 1 to 2 parts of silane coupling agent KH-171.
[0006] Furthermore, the modified graphite nano powder is obtained by secondary air flow crushing of graphite, and the particle size is 50 to 90 nm.
[0007] Furthermore, the graphite particle size is 0.1 to 1 mm.
[0008] Furthermore, the working pressure of the secondary air flow crushing is 0.98-1.02MPa, and the required air volume is 2-4m 3 / min, wherein the first air flow crushing uses H2O2 gas, the processing temperature is 200-300°C, the particle size after crushing is 1-10μm, and the second air flow crushing uses 1,4-butenediol gas.
[0009] Furthermore, the 1,4-butenediol gas is obtained from a 20 wt% 1,4-butenediol / ethanol solution by bubbling with compressed air.
[0010] Furthermore, the preparation method of the modified polyurethane emulsion is:
[0011] (1) 4-6 g of 3-hydroxy-1-naphthylamine and 1-3 g of sodium hydroxide are added to 60 mL of aqueous solution, and the mixture is kept at -5°C in an ice-salt bath. 1-3 g of sodium nitrite is added, and 10-15 mL of 50 wt% sulfuric acid is added dropwise over 70 min while stirring at 60-80 rpm. After the addition is complete, the mixture is kept at -3°C and stirred for 1 h. The solid is filtered to obtain the solid, and then filtered and washed with water until the pH of the filtrate is neutral. The solid is dried at 50°C to a constant weight to obtain a nitrosylated product.
[0012] (2) 4-6 g of the nitrosated product was dissolved in 140 mL of ethanol. The mixture was heated to 90° C. in a nitrogen atmosphere, kept warm for 15 min, and then a mixed solution consisting of 4-6 g of 1,3,3-trimethyl-2-methyleneindolyl-5-amine and 25 mL of ethanol was added dropwise within 30 min. The mixture was stirred at 80 rpm for 5 h, and then activated carbon of 5% by mass of the reaction solution was added. The mixture was kept warm for 15 min, filtered while hot, and the filtrate was distilled under reduced pressure to remove ethanol. The mixture was naturally cooled and allowed to stand for 8 h. The precipitated solid was filtered and washed with ethanol 6 times, and dried at 50° C. to constant weight to obtain a spirooxazine compound.
[0013] (3) 20-22 g of dimethyl carbonate and 2-3 g of spirooxazine compound were mixed, heated to 75° C. in a water bath, and then 1.0-2.2 g of lead nitrate was added. The mixture was reacted at constant temperature for 2 h. After the reaction was completed, the mixture was filtered while hot, and the filtrate was allowed to stand at 10° C. for 2 h. The solid was filtered to obtain intermediate A.
[0014] (4) 5-7 g of intermediate A and 52-55 g of 30% sulfuric acid solution were fully stirred and mixed, the temperature was raised to 50° C., 1-3 mL of formaldehyde was added, the air in the reaction kettle was replaced with nitrogen, and then nitrogen was filled to 0.3 MPa, the temperature was raised to 180° C., and the reaction was carried out at a reaction pressure of 1.5 MPa for 6 h, then cooled and filtered. The obtained solid was washed with ethanol 6 times and dried at 60° C. to constant weight to obtain an isocyanate compound;
[0015] (5) 8-35 g of polyether diol and 10-20 g of 2,4-dihydroxy-butyric acid are mixed, and the temperature is raised to 60-90° C. under a nitrogen atmosphere and uniform stirring at a speed of 200 rpm. 3-20 g of isocyanate compound and 0.1-0.2 g of dibutyltin dilaurate are added, and the mixture is reacted for 1-3 h. Then, 5 g of 4,5-dihydroxy-2-enoic acid and 10-20 g of acetone are added, and the mixture is reacted at 50-70° C. for 2-5 h. The mixture is cooled to 40° C., 1-1.8 g of triethylamine is added, and the reaction is continued for 30 min. Then, 86-150 g of deionized water and 0.8-1.0 g of ethylenediamine are added, and the rotation speed is increased to 1500 r / min. The mixture is stirred for 30 min, and the acetone is removed by rotary evaporation to obtain an aqueous polyurethane emulsion.
[0016] Furthermore, the molecular weight of the polyether diol in step (5) is between 1000 and 4000.
[0017] Furthermore, the colorant is an inorganic pigment of 600-800 mesh.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present invention uses 3-hydroxy-1-naphthylamine as a raw material, introduces a nitro group at the ortho position of the hydroxyl group through nitrosation, and on this basis, relies on the nitro group and the hydroxyl group to combine with 1,3,3-trimethyl-2-methyleneindoline-5-amine to form a spirooxazine compound with amino groups at both ends, and then after the amino groups at both ends are isocyanated, they are polymerized with 4,5-dihydroxy-2-hexenoic acid and 2,4-dihydroxy-butyric acid to form polyurethane. The present invention introduces a photochromic group into the polyurethane molecular chain, and compared with adding a photochromic agent alone, it can be better compatible with various raw materials. This can extend the effective period of the photochromic effect and prevent the photochromic components from being separated out and deteriorating due to long-term use. The photochromic group contains a multi-benzene ring structure, which can greatly improve the water resistance of the ink after curing. In addition, the present invention selects 4,5-dihydroxy-2-enoic acid and 2,4-dihydroxy-butyric acid as polyol compounds, and introduces multiple carboxyl groups into the polyurethane molecular chain at the same time, which can improve its hydrophilicity, so that the ink exists in an aqueous system without organic volatiles, which can reduce pollution to the environment and improve the adsorption of the ink.
[0020] The invention uses graphite as a raw material, firstly utilizes H2O2 hot air flow to break it, realizes the initial reduction of particle size, and at the same time increases the number of oxygen-containing groups on the graphite surface and increases active adsorption sites, and then utilizes 1,4-butenediol air flow to perform secondary breaking to realize graphite nano-crystallization, so that after the ink is solidified, a flat and smooth surface is formed, and the abrasion resistance of the ink is effectively improved. At the same time, 1,4-butenediol is grafted to the graphite surface by chemical bonds to ensure its dispersibility in the aqueous system, and at the same time, the ink composition constructed with modified polyurethane and propylene compounds, when in use, each of the three carries a double bond, can react and polymerize with oxygen in the air to form a three-dimensional network structure, so that the handwriting is quickly completely dried from a liquid material to a solid, and has excellent quick-drying property, and the graphite has a heat absorption effect, which promotes the surface temperature of the handwriting to accelerate the evaporation rate of residual water, and at the same time forms a dense film structure after quick drying to wrap the graphite nanoparticles, and the graphite itself has a self-lubricating property, so a good synergistic effect is produced to improve the wear resistance of the ink. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods for various indicators of the ink prepared in the following examples are as follows:
[0023] Quick drying: Use scraping method to make samples, dry them at 60℃, print the ink with a thickness of 5μm, and test the time when the moisture drops to trace amount (completely dry).
[0024] Wear resistance: The Gakushin type friction resistance (up and down swing) is measured by a Japanese-made Gakushin type abrasion resistance tester, and the test conditions are: 500g / 10 back and forth, and the result is determined: the grade values of (poor) 1-3-5 (excellent) represent the grade gears from poor to excellent; the swing type abrasion resistance (left and right swing) is measured by a swing type abrasion resistance tester, and the test conditions are: 4 pounds / 50 back and forth, and the result is determined: the grade values of (poor) 1-3-5 (excellent) represent the grade gears from poor to excellent; the vibration type abrasion resistance is measured by a vibration type abrasion resistance tester, and the result is determined: the grade values of (poor) 1-3-5 (excellent) represent the grade gears from poor to excellent.
[0025] Adhesion: Prepare the same batch of nylon plates, the size of the plastic plate is 50×50 mm, divide them into several groups, apply the ink of the embodiment and the comparative example on the nylon plates of the corresponding groups, the coating area is 30×30 mm, use a utility knife to divide the coating area into small grids of 3×3 mm, stick the 3M800 test tape tightly on the test part, cover the entire test area, wait for 5 minutes, tear off the tape at a 45° angle to the plastic plate, repeat 3 times, check the deoiling area, take the ratio of the deoiling area to the experimental area as the test result, and record the average value.
[0026] Example 1
[0027] A friction-resistant quick-drying odorless ink, which comprises, by weight, 8 parts of modified graphite nanopowder, 25 parts of modified polyurethane emulsion, 20 parts of acrylic emulsion, 15 parts of water, 0.1 parts of organosilicon leveling agent, 3 parts of inorganic pigment with a particle size of 800 mesh, 0.1 parts of organosilicon defoaming agent, and 1 part of silane coupling agent KH-171;
[0028] The modified graphite nano powder is obtained by secondary air flow crushing of graphite with a particle size of 0.8 mm. The working pressure of the secondary air flow crushing is 1.0 MPa and the required air volume is 4 m 3 / min, wherein the first air flow crushing uses H2O2 gas, the treatment temperature is 300°C, and the particle size after crushing is 5μm, and the second air flow crushing uses 1,4-butenediol gas, which is obtained by bubbling 20wt% 1,4-butenediol / ethanol solution through compressed air, and the particle size after crushing is 90nm;
[0029] The preparation method of the modified polyurethane emulsion is:
[0030] (1) 5.2 g of 3-hydroxy-1-naphthylamine and 2.8 g of sodium hydroxide were added to 60 mL of aqueous solution, and the mixture was kept at -5°C in an ice-salt bath. 1.0 g of sodium nitrite was added, and 15 mL of 50 wt% sulfuric acid was added dropwise over 70 min under stirring at 80 rpm. After the addition was completed, the mixture was kept at -3°C and stirred for 1 h. The solid was filtered and then washed with water while being filtered until the pH of the filtrate was neutral. The solid was dried at 50°C to constant weight to obtain a nitrosylated product.
[0031] (2) 5.6 g of the nitrosated product was dissolved in 140 mL of ethanol. The mixture was heated to 90° C. in a nitrogen atmosphere, kept warm for 15 min, and then a mixed solution consisting of 5.2 g of 1,3,3-trimethyl-2-methyleneindolyl-5-amine and 25 mL of ethanol was added dropwise within 30 min. The mixture was stirred at 80 rpm for 5 h, and then 5% of the mass of the reaction solution was added with activated carbon. The mixture was kept warm for 15 min, filtered while hot, and the filtrate was distilled under reduced pressure to remove ethanol. The mixture was naturally cooled and allowed to stand for 8 h. The precipitated solid was filtered and washed with ethanol 6 times, and dried at 50° C. to constant weight to obtain a spirooxazine compound.
[0032] (3) 22 g of dimethyl carbonate and 2.5 g of spirooxazine compound were mixed, heated in a water bath to 75° C., and then 2.0 g of lead nitrate was added. The mixture was reacted at constant temperature for 2 h. After the reaction was completed, the mixture was filtered while hot, and the filtrate was allowed to stand at 10° C. for 2 h. The solid was filtered to obtain intermediate A.
[0033] (4) 7 g of intermediate A and 53.5 g of 30% sulfuric acid solution were fully stirred and mixed, the temperature was raised to 50° C., 1.5 mL of formaldehyde was added, the air in the reactor was replaced with nitrogen, and then nitrogen was filled to 0.3 MPa, the temperature was raised to 180° C., and the reaction was carried out at a reaction pressure of 1.5 MPa for 6 h, then cooled and filtered. The obtained solid was washed with ethanol 6 times and dried at 60° C. to constant weight to obtain an isocyanate compound;
[0034] (5) 28 g of polyether diol and 20 g of 2,4-dihydroxy-butyric acid were mixed, and the temperature was raised to 75° C. under a nitrogen atmosphere and uniform stirring at a speed of 200 rpm. 12 g of isocyanate compound and 0.1 g of dibutyltin dilaurate were added, and the mixture was reacted for 2.5 h. Then, 5 g of 4,5-dihydroxy-2-enoic acid and 15 g of acetone were added, and the mixture was reacted at 65° C. for 5 h. The mixture was cooled to 40° C., 1.05 g of triethylamine was added, and the reaction was continued for 30 min. Then, 150 g of deionized water and 0.8 g of ethylenediamine were added, and the rotation speed was increased to 1500 r / min. The mixture was stirred for 30 min, and the acetone was removed by rotary evaporation to obtain an aqueous polyurethane emulsion.
[0035] The friction-resistant quick-drying odorless ink print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed; the ink is stored for one month before printing, and the print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed.
[0036] Example 2
[0037] The difference between Example 2 and Example 1 is: 10 parts of modified graphite nanopowder, 30 parts of modified polyurethane emulsion, 25 parts of acrylic emulsion, 12 parts of water, 0.1 parts of silicone leveling agent, 4 parts of inorganic pigment with a particle size of 800 mesh, 0.1 parts of silicone defoaming agent, and 1 part of silane coupling agent KH-171; the remaining steps are the same as Example 1.
[0038] The friction-resistant quick-drying odorless ink print changes color within 15 seconds when exposed to sunlight, and returns to colorless within 4 minutes when the light is removed; the ink is stored for one month and then printed, and the print changes color within 15 seconds when exposed to sunlight, and returns to colorless within 4 minutes when the light is removed.
[0039] Example 3
[0040] The difference between Example 3 and Example 1 is: 12 parts of modified graphite nanopowder, 35 parts of modified polyurethane emulsion, 30 parts of acrylic emulsion, 15 parts of water, 0.3 parts of silicone leveling agent, 5 parts of inorganic pigment with a particle size of 800 mesh, 0.3 parts of silicone defoaming agent, and 2 parts of silane coupling agent KH-171; the remaining steps are the same as Example 1.
[0041] The friction-resistant quick-drying odorless ink print changes color within 15 seconds when exposed to sunlight, and returns to colorless within 4 minutes when the light is removed; the ink is stored for one month and then printed, and the print changes color within 15 seconds when exposed to sunlight, and returns to colorless within 4 minutes when the light is removed.
[0042] Comparative Example 1
[0043] The difference between Comparative Example 1 and Example 1 is that: in parts by weight, the friction-resistant quick-drying odorless ink includes 8 parts of modified graphite nanopowder, 25 parts of aqueous polyurethane emulsion, 20 parts of acrylic emulsion, 15 parts of water, 0.1 parts of silicone leveling agent, 3 parts of inorganic pigment with a particle size of 800 mesh, 0.1 parts of silicone defoaming agent, 1 part of silane coupling agent KH-171, and 3 parts of optical variable powder; the preparation method of the aqueous polyurethane emulsion is: 28g of polyether diol and 20g of 2,4-dihydroxy-butyric acid are mixed, heated to 75°C under nitrogen atmosphere and uniform stirring at a speed of 200rpm, 12g of IPDI (or TDI) and 0.1g of dibutyltin dilaurate are added, reacted for 2.5h, and then 5g of 4,5-dihydroxy-2-hexenoic acid and 15 g of acetone were reacted at 65 ° C for 5 h, then cooled to 40 ° C, 1.05 g of triethylamine was added, and the reaction was continued for 30 min. Then, 150 g of deionized water and 0.8 g of ethylenediamine were added, and the speed was increased to 1500 r / min. The mixture was stirred for 30 min, and the acetone was removed by rotary evaporation to obtain an aqueous polyurethane emulsion. The remaining steps were the same as those in Example 1.
[0044] The friction-resistant quick-drying odorless ink print changes color within 1 minute under sunlight, and returns to colorless within 10 minutes after the light is removed; the ink is stored for 1 month and then printed, and the print changes color within 3 minutes under sunlight and becomes lighter.
[0045] Comparative Example 2
[0046] The difference between Comparative Example 2 and Example 1 is that 4,5-dihydroxy-2-hexenoic acid is not added in the preparation of the modified polyurethane emulsion; the remaining steps are the same as Example 1.
[0047] The friction-resistant quick-drying odorless ink print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed; the ink is stored for one month before printing, and the print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed.
[0048] Comparative Example 3
[0049] The difference between Comparative Example 3 and Example 1 is that 2,4-dihydroxy-butyric acid is not added in the preparation of the modified polyurethane emulsion; the remaining steps are the same as Example 1.
[0050] The friction-resistant quick-drying odorless ink print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed; the ink is stored for one month before printing, and the print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed.
[0051] Comparative Example 4
[0052] The difference between Comparative Example 4 and Example 1 is that the graphite is not subjected to the first air flow crushing in the preparation of the modified graphite nanopowder; the remaining steps are the same as those in Example 1.
[0053] The friction-resistant quick-drying odorless ink print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed; the ink is stored for one month before printing, and the print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed.
[0054] Comparative Example 5
[0055] The difference between Comparative Example 5 and Example 1 is that the graphite is not subjected to a second air flow crushing in the preparation of the modified graphite nanopowder; the remaining steps are the same as those in Example 1.
[0056] The friction-resistant quick-drying odorless ink print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed; the ink is stored for one month before printing, and the print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed.
[0057] Comparative Example 6
[0058] The difference between Comparative Example 6 and Example 1 is that wax powder is used instead of modified graphite nanopowder; the remaining steps are the same as Example 1.
[0059] The friction-resistant quick-drying odorless ink print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed; the ink is stored for one month before printing, and the print changes color within 30 seconds when exposed to sunlight, and returns to colorlessness within 5 minutes when the light is removed.
[0060] Effect example
[0061] Table 1 below shows the performance analysis results of the inks of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0062] Table 1
[0063]
[0064]
[0065] The present invention introduces a photochromic group into a polyurethane molecular chain, which can be better compatible with various raw materials than adding a photochromic agent alone, thereby extending the effective period of the photochromic agent and preventing the photochromic component from being separated out and deteriorating due to long-term use. In addition, the present invention selects 4,5-dihydroxy-2-hexenoic acid and 2,4-dihydroxy-butyric acid as polyol compounds to improve the hydrophilicity of the polyurethane, thereby allowing the ink to exist in an aqueous system without containing organic volatiles, thereby reducing pollution to the environment and improving the adsorption of the ink. The invention uses graphite as a raw material, and sequentially utilizes H2O2 hot air flow and 1,4-butenediol air flow for secondary crushing to realize nano-scale graphite. Meanwhile, the graphite can react and polymerize with modified polyurethane and propylene compounds and oxygen in the air to form a three-dimensional network structure, so that the writing can be quickly and completely dried from a liquid material to a solid, and has excellent quick-drying properties. Graphite has a heat absorption effect, which promotes the surface temperature of the writing to increase, accelerates the evaporation rate of residual water, and forms a dense film structure after quick drying to wrap graphite nanoparticles therein. Graphite itself has self-lubricating properties, so a good synergistic effect is produced to improve the wear resistance of the ink.
[0066] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A friction-resistant quick-drying odorless ink, characterized in that: The friction-resistant quick-drying odorless ink comprises, by weight, 8 to 12 parts of modified graphite nanopowder, 25 to 35 parts of modified polyurethane emulsion, 20 to 30 parts of acrylic emulsion, 10 to 15 parts of water, 0.1 to 0.3 parts of organosilicon leveling agent, 3 to 5 parts of colorant, 0.1 to 0.3 parts of organosilicon defoaming agent, and 1 to 2 parts of silane coupling agent KH-171.
2. The friction-resistant quick-drying odorless ink according to claim 1, characterized in that: The modified graphite nano powder is obtained by secondary air flow crushing of graphite, and the particle size is 50-90nm.
3. The friction-resistant quick-drying odorless ink according to claim 2, characterized in that: The graphite particle size is 0.1-1 mm.
4. The friction-resistant quick-drying odorless ink according to claim 2, characterized in that: The working pressure of the secondary air flow crushing is 0.98-1.02MPa, and the required air volume is 2-4m 3 / min, wherein the first air flow crushing uses H2O2 gas, the processing temperature is 200-300°C, the particle size after crushing is 1-10μm, and the second air flow crushing uses 1,4-butenediol gas.
5. The friction-resistant quick-drying odorless ink according to claim 4, characterized in that: The 1,4-butenediol gas is obtained from a 20 wt % 1,4-butenediol / ethanol solution by bubbling with compressed air.
6. The friction-resistant quick-drying odorless ink according to claim 1, characterized in that: The preparation method of the modified polyurethane emulsion is: (1) 4-6 g of 3-hydroxy-1-naphthylamine and 1-3 g of sodium hydroxide are added to 60 mL of aqueous solution, and the mixture is kept at -5°C in an ice-salt bath. 1-3 g of sodium nitrite is added, and 10-15 mL of 50 wt% sulfuric acid is added dropwise over 70 min while stirring at 60-80 rpm. After the addition is complete, the mixture is kept at -3°C and stirred for 1 h. The solid is filtered to obtain the solid, and then filtered and washed with water until the pH of the filtrate is neutral. The solid is dried at 50°C to a constant weight to obtain a nitrosylated product. (2) 4-6 g of the nitrosated product was dissolved in 140 mL of ethanol. The mixture was heated to 90° C. in a nitrogen atmosphere, kept warm for 15 min, and then a mixed solution consisting of 4-6 g of 1,3,3-trimethyl-2-methyleneindolyl-5-amine and 25 mL of ethanol was added dropwise within 30 min. The mixture was stirred at 80 rpm for 5 h, and then activated carbon of 5% by mass of the reaction solution was added. The mixture was kept warm for 15 min, filtered while hot, and the filtrate was distilled under reduced pressure to remove ethanol. The mixture was naturally cooled and allowed to stand for 8 h. The precipitated solid was filtered and washed with ethanol 6 times, and dried at 50° C. to constant weight to obtain a spirooxazine compound. (3) 20-22 g of dimethyl carbonate and 2-3 g of spirooxazine compound were mixed, heated to 75° C. in a water bath, and then 1.0-2.2 g of lead nitrate was added. The mixture was reacted at constant temperature for 2 h. After the reaction was completed, the mixture was filtered while hot, and the filtrate was allowed to stand at 10° C. for 2 h. The solid was filtered to obtain intermediate A. (4) 5-7 g of intermediate A and 52-55 g of 30% sulfuric acid solution were fully stirred and mixed, the temperature was raised to 50° C., 1-3 mL of formaldehyde was added, the air in the reaction kettle was replaced with nitrogen, and then nitrogen was filled to 0.3 MPa, the temperature was raised to 180° C., and the reaction was carried out at a reaction pressure of 1.5 MPa for 6 h, then cooled and filtered. The obtained solid was washed with ethanol 6 times and dried at 60° C. to constant weight to obtain an isocyanate compound; (5) 8-35 g of polyether diol and 10-20 g of 2,4-dihydroxy-butyric acid are mixed, and the temperature is raised to 60-90° C. under a nitrogen atmosphere and uniform stirring at a speed of 200 rpm. 3-20 g of isocyanate compound and 0.1-0.2 g of dibutyltin dilaurate are added, and the mixture is reacted for 1-3 h. Then, 5 g of 4,5-dihydroxy-2-enoic acid and 10-20 g of acetone are added, and the mixture is reacted at 50-70° C. for 2-5 h. The mixture is cooled to 40° C., 1-1.8 g of triethylamine is added, and the reaction is continued for 30 min. Then, 86-150 g of deionized water and 0.8-1.0 g of ethylenediamine are added, and the rotation speed is increased to 1500 r / min. The mixture is stirred for 30 min, and the acetone is removed by rotary evaporation to obtain an aqueous polyurethane emulsion.
7. The friction-resistant quick-drying odorless ink according to claim 6, characterized in that: The molecular weight of the polyether diol in step (5) is between 1000 and 4000.
8. The friction-resistant quick-drying odorless ink according to claim 1, characterized in that: The colorant is an inorganic pigment with a mesh size of 600 to 800.
9. A method for preparing a friction-resistant, quick-drying, odorless ink according to any one of claims 1 to 8, characterized in that: The ink is obtained by uniformly mixing the raw materials of the friction-resistant quick-drying odorless ink.
Citation Information
Patent Citations
Water-based quick-drying ink composition for gravure
CN105968943A
Water-soluble indoline spironaphthoxazine quaternary ammonium salt additive, preparation method and application thereof
CN106928254A
Cross-linked polyurethane containing photochromic spirooxazine and application
CN108102064A
Photochromic wear-resistant waterborne polyurethane ink
CN114479555A
Aluminum foil printing water-based ink and preparation process thereof
CN117946546A